Unveiling Reproductive Oppression: An In-depth Analysis of Radical Feminism in Joyland - Riaz, Filza; Chan, Turs Mohi Ud Din (Pakistan Languages and Humanities Review, 2024)
This research analyzes the portrayal of reproductive oppression, a persisting societal issue in a Pakistani drama film, named Joyland. Radical feminism emerged in the mid-20th century as a branch of the second wave of feminism and offers a powerful framework to comprehend and tackle this issue. Rooted in the belief that women’s oppression stems from patriarchal dominance, Shulamith Firestone advocates for restructuring society to dismantle this power and liberate women in her book The Dialectic of Sex: The Case for Feminist Revolution. Analyzing Joyland through her feminist lens, this research delves into the root causes of reproductive oppression by exploring how ingrained patriarchal norms relegate women’s bodies. The film is treated as a text of its own, analyzing its staging, grammar, and emotional portrayal to unravel the patriarchal branch it critiques. The results reveal how patriarchy as described by Firestone in Joyland confines women to restrictive roles and deprives them of control over their own bodies. The research also incorporates radical feminist principles in cultural discourse and policymaking to deal with reproductive oppression, advocating for systemic changes that empower women to gain freedom and autonomy.